Mission France : the true history of the women of SOE - Vigurs, Kate (New Haven : Yale University Press, 2021)
The full story of the thirty-nine female SOE agents who went undercover in France
Frontmatter -- CONTENTS -- List of Illustrations -- List of Abbreviations -- The Women Agents of F Section -- Map of Infiltrations/Landings -- Prologue -- PART I: FOUNDATIONS -- 1 Setting Europe Ablaze -- 2 Trailblazers -- PART II: WAR -- 3 The Fall of PROSPER -- 4 The Army of Shadows -- 5 D-Day -- 6 Incarceration -- PART III: DEATH AND DELIVERANCE -- 7 Night and Fog -- 8 Ravensbrück -- 9 Aftermath -- Epilogue -- Appendix: George Cross Citations -- Notes -- Bibliography -- Acknowledgements -- Index
Includes bibliographical references and index
Description based on online resource; title from PDF title page (De Gruyter, viewed on June 04, 2021)
JSTOR
Keywords: Great Britain. -- Special Operations Executive. -- F Section; Great Britain. -- Special Operations Executive. -- F Section; World War, 1939-1945 -- Underground movements -- France; World War, 1939-1945 -- Secret service -- Great Britain; World War, 1939-1945 -- Women; Guerre mondiale, 1939-1945 -- Mouvements de résistance -- France; Guerre mondiale, 1939-1945 -- Service secret -- Grande-Bretagne.; Guerre mondiale, 1939-1945 -- Femmes; HISTORY / Military / World War II; Secret service; War -- Underground movements; Women; France; Great Britain; 1939-1945